IDENTIFICATION OF OXIDATION PRODUCTS IN EDIBLE OIL BY MEANS OF 1H NMR SPECTROSCOPY - COLZATO, MARINA; FORATO, LUCIMARA A.; COLNAGO, LUIZ A.; ASSIS, ODILIO B. G. (Revista Brasileira de Engenharia de Biossistemas, 2009)
The hydrogen magnetic resonance spectroscopy (1H NMR) is a powerful tool for monitoring oxidationproducts in edible oils. This method is fast, simple and reliable, useful for evidencing and identifyingprimary oxidation products such as hydroperoxides and conjugated dienes. In this study, canola, oliveand macadamia oils underwent accelerated oxidation along 30 days and the oxidation products analy-sis by 1H NMR. The results show higher stability (resistance to thermal stress) to the olive oil > macad-amia > canola respectively.